The role of ultrasound densitometry for screening diagnostics of osteopenia in children with juvenile idiopathic arthritis - Ilchenko, Svitlana; Fialkovska, Anastasiia; Makoviichuk, Oleksii (ScienceRise: Medical Science, 2024)
Juvenile idiopathic arthritis (JIA) in children remains one of the most severe medical and social problems in the world. One of the complications of the disease is the development of osteopenic syndrome (OS) with the possible formation of osteoporosis. Therefore, in the process of monitoring patients with JIA, it is necessary to monitor the structural and functional state of bone tissue. The aim of the study was to determine the role of ultrasound densitometry (UD) for the screening diagnosis of OS in children with JIA. Materials and methods: examined 63 children with JIA aged 5 to 18 years. All patients underwent a general clinical examination and determination of the serum content of 25 hydroxyvitamin D (25 (OH) D) and UD to assess the mineral density of bone tissue. Results. In children with JIA, 41.76 % of cases were diagnosed with OS of various degrees of severity, which corresponds to the results of many studies conducted using such a "gold standard" of diagnosis as dual-energy X-ray absorptiometry (DXA). At the same time, osteopenia I degree was diagnosed in 20.0 % of cases, II degree – in 35.0 % of cases, III degree – in 30.0 % of cases, and in 3 patients (15.0 %) the Z-index was below -2 .5, which meets the criteria for osteoporosis. It was established that children with OS were older than children without this syndrome, significantly more often complained of pain in the joints, morning stiffness and restriction of movements, and during examination, joint deformity was more often detected in them. In addition, children with OS were characterized by a significantly lower level of 25 (OH)D in blood serum (17.3 [14.3, 25.8] vs 28.8 [20.6, 46.3] ng/ml; p< 0.05). Conclusions. UD can be used for screening diagnosis of OS in children with JIA. The ease of use of ultrasound densitometry devices, the absence of radiation exposure of the child, the possibility of conducting an examination at the bedside, and the low cost are clear advantages of this method of examining bone mineral density compared to DXA